Noninvasive ventilation utilization in the Kingdom of Saudi Arabia: Results of a national survey - Mohammed Dhafer AlAhmari; Hajed Al-Otaibi; Hatem Qutub; Ibrahim AlBalawi; Abdullah Alqahtani; Bandar Almasoudi (Annals of Thoracic Medicine, 2018)
INTRODUCTION: Noninvasive ventilation (NIV) has been extensively used globally and is often administered as the first-line treatment. Currently, data regarding the utilization of NIV in the Kingdom of Saudi Arabia (KSA) is scarce. The present study aimed to assess and quantify the utilization of NIV in clinical practice across the KSA and investigate obstacles that may cause NIV underutilization. METHODS: A web-based survey composed of a 31-item, self-administered questionnaire was developed and validated. The questionnaire was designed to obtain general information about each hospital, availability of NIV practice, use of NIV, and obstacles that can hinder NIV use in clinical settings; the survey was sent to senior respiratory therapists (RTs) of 76 hospitals. Descriptive statistics were used to analyze the data. RESULTS: Sixty-one hospitals (80.3%) responded to the survey (47 governmental and 14 private). NIV was available in all hospitals and all the Intensive Care Units. The majority of RTs (85%) reported having a good experience with NIV, with a confidence rate of 60%; however, only 22% of the RTs had received formal training. Although NIV setup was the sole responsibility of RTs, only 69% participated in NIV management. Moreover, 72% of hospitals had an NIV setup protocol in place. However, 50% of them lacked a protocol for NIV failure. NIV protocols for specific indications were present in 64% of the hospitals: 47.2% for monitoring and 42% for weaning. The perceived efficiency of NIV practice was low in the medical wards, with a <49% success rate in 39% of the hospitals. Shortage of staff and lack of formal training were the most common reasons for NIV underutilization. CONCLUSION: The efficiency of NIV in the KSA was low. The RTs expressed moderate confidence in administering NIV. Lack of appropriate exposure and formal training could have negative impacts on NIV practice.